2003
DOI: 10.1001/archotol.129.1.113
|View full text |Cite
|
Sign up to set email alerts
|

DentaScan as an Accurate Method of Predicting Mandibular Invasion in Patients With Squamous Cell Carcinoma of the Oral Cavity

Abstract: DentaScan is an accurate method of preoperative evaluation for mandibular invasion in patients with SCC of the oral cavity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 15 publications
0
31
1
1
Order By: Relevance
“…6e8, 11 Mukherji et al 11 reported a sensitivity of 96%, specificity of 87%, and NPV of 95% for mandibular erosion in oral cavity SCCs using 3 mm sections on a conventional non-helical scanner with bone and soft-tissue algorithms. Brockenbrough et al 12 using DentaScan in oral cavity SCC reported a sensitivity of 95%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6e8, 11 Mukherji et al 11 reported a sensitivity of 96%, specificity of 87%, and NPV of 95% for mandibular erosion in oral cavity SCCs using 3 mm sections on a conventional non-helical scanner with bone and soft-tissue algorithms. Brockenbrough et al 12 using DentaScan in oral cavity SCC reported a sensitivity of 95%.…”
Section: Discussionmentioning
confidence: 99%
“…21 Vidiri et al 20 analysed bone algorithms with axial images, but multiplanar reformats were not employed. Brockenbrough et al 12 in their study using DentaScan acquired only bone algorithm images without soft-tissue windows or contrast medium injection, and reported a specificity of 79%. Imaizumi et al 19 used both bone and soft-tissue algorithms along with dental CT images (DentaScan), which yielded a higher specificity (88%).…”
Section: Ct Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…6 For this reason, clinical examination must be complemented by radiological examination 7 for the assessment of size, thickness and depth of the tumour 8 as well as the degree of bone tissue invasion. [9][10][11] This bone tissue invasion detection, cortical or medullary, is indicative of a T4 tumour stage. 12 At this stage, the 5 year survival rate is close to 50%, whether treatment is surgical resection (47% survival) 13 or chemotherapy (56% survival).…”
Section: Introductionmentioning
confidence: 99%
“…Tumour infi ltration to the mandible is demonstrated as the loss of normal low signal intensity from the cortical bone 5 . MDCT scans with Denta scan may offer an excellent technique for the evaluation of bone erosion from tumour 19 . However, studies reported variations in the diagnostic accuracy of MDCT and MRI in detecting mandibular invasion 7,20,21 .…”
Section: Discussionmentioning
confidence: 99%